Distribution and abundance of gelatinous zooplankton along Tamil Nadu coastal waters - G., Iyyapparajanarasimapallavan; P., Sampath Kumar; C., Prasanna Kumar; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman; John, Akbar (Asian Network for Scientific Information, 2013)
The distribution and abundance of the gelatinous zooplankton namely hydromedusae, scyphomedusae, siphonophore, ctenophore, salps, doliolids, appendicularians and chaetognaths were investigated in two seasons at seven stations in East Tamil Nadu coast, India. The occurrences of gelatinous zooplankton were observed to be more in summer than in winter. However, the composition of different species in each group varied from all the stations and seasons. Apart from the individual variation in seasonal distribution, most of the species appeared to be cosmopolitan in the Indian waters. A total of 34 species from summer and 17 species from winter were recorded during the present study. The hydromedusae were dominant in both the seasons of the study period. Ephyrae of the scyphomedusae were also noticed in both the seasons.